Yāsīn dalam Interpretasi Bisri Musthofa: Meninjau Tafsir Yāsīn dan Tafsir Al-Ibrīz Terhadap Tafsir Lafadz Yāsīn - Khakim, Lukman; Rohman, Moch. Abdul (LPPM IAI Hasanuddin Pare-Kediri, 2024)
Fawātiḥus suwar is a part of the ulumul Quran that studies the beginning of surahs and letters including muqaththa'ah (letters that are cut off) such as qāf, nūn, and yāsīn. This study is very much debated among scholars about its meaning, because muqaththa'ah letters include mutasyābihāt verses (polysemous verses and often cannot be understood). In this case, Kyai Bisri Mustofa is interesting to study because he tries to interpret the letter yāsīn through his two commentaries (Tafsīr Surah Yāsīn and al-Ibrīz). This study is to examine Bisri Mustofa's interpretation of lafadz yāsīn, as well as to trace the relationship between the two interpretations.